Hubungan Antara Kinerja Lingkungan dan Kualitas Pengungkapan Lingkungan dengan Kinerja Ekonomi Perusahaan di Indonesia - Lindrianasari Lindrianasari (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2007)
This study investigated environmental performance, environmental dis¬closure and eco¬nomic performance by 88 Indonesian companies in 2004. We evalu¬ated interrelations among envi¬ron¬mental performance, environmental disclosure and economic performance by using regression. We obtain result that environmental performance is positively and significantly related to environmental disclosure and also economic performance (Debt to Equity Ratio/DER, Export, Ownership, Margin and Age) is positively associated with environmental performance and environ¬mental disclosure but we found insufficient statistical significance to accept second and third hypothesis. Keywords: environmental performance, environmental disclosure, economic per¬formance.